Prefixes of Attitude in the Class-Changing Function in the English Language - Pantić, Irena M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper analyses the group of prefixes of orientation and attitude. Paying due attention to the primary prefixal role in influencing the meaning of the root the prefix is attached to, the paper focuses on examining the capability of the prefixes to affect the class of the root, as well. The research corpus was sourced from the Oxford English Dictionary Online. OED eases the process of compiling the language samples by tracing a word’s origin, revealing its earliest known use, calculating its frequency, and helping a user plot the word’s subsequent development in English. Above all else, its etymological data help a researcher track the structure of the word and hence give a reliable clue about the class of the root and its derivation. The corpus comprises 163 sample lexemes. The lexemes were derived from an existing word root by adding one of the five identified prefixes of attitude—anti-, pro-, co-, contra- and counter-. These prefixes as bound morphemes construct new words and produce new meanings. Their meanings vary from in-principle acceptance (co-, pro-) to contestation (anti-, counter-, contra-) of what was determined by the root. The research supported the hypothesis that besides the semantic modification, the prefixes of attitude displayed an untypical derivational capacity—they change the class (a syntactic category) of the root, making a noun into a verb, a verb into an adjective, an adjective into a noun, etc. It also showed an uneven distribution of the prefixes of attitude across the corpus. Anti- in 91 examples (55.8%) and pro- in 50 (30.6%) took primacy over the other three prefixes. The class-changing capacity of counter-, co- and contra- is weaker but yet present—counter- in 12 examples (7.4%), co- in 6 (3.7%) and contra- in 4 (2.5%). This analysis also identified some other trends. Such prefixal untypicality was attested only with verbs, nouns and adjectives, but not with other word classes. The most common class-changing type is deriving adjectives from nouns (68%). It is present with each of the five prefixes, especially when a noun has no adjectival counterpart, in either derived or referential form. Such a denominal adjective premodifies the phrase it comes immediately before. The second most common class-changing type is deriving nouns from adjectives (16%). It is also present with each prefix. In this way, a deadjectival noun refers to an agent who advocates or opposes the characteristics or attitudes denoted by the input adjective. The analysis also indicates that such derivatives have continuously arisen during the 19th, 20th and 21st centuries, therefore the productivity of such a derivation type is stable. On the other hand, individual derivatives occur from obsolete and very rare to about 0.1 times (3/8) per million words in typical modern English usage. Occasional deviations may occur up to 1 time (4/8, counter-terror, antivirus) and maximally up to 100 times (6/8, antibiotic) per million words. As the above result suggests, this formation pattern is not greatly influential and productive but it has potential.